Certain Factor Analysis for Extra Pulmonary Tuberculosis Diagnosis - Ramadiani Ramadiani; Nur Aini; Heliza Rahmania Hatta; Fahrul Agus; Zainal Ariffin; Azainil Azainil (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
Tuberculosis is an infectious disease that is easily transmitted through the air. Tuberculosis mostly attacks the lungs, but this disease can also attack other organs called extra- pulmonary. The Extra pulmonary tuberculosis can endanger the safety of community and slow in initial diagnosis because of the lack of knowledge. The purpose of this research is to build expert system of the extra pulmonary tuberculosis disease diagnosis. The system can facilitate the user in making the initial diagnosis of the disease, so patients can get the right handling. The system uses forward chaining inference and a Web-based Certainty Factor method with an accuracy rate of 85% has been utilized to assist health and community.